Spanish for dummies - Wald, Susana (Wiley Publishing, Inc., 2006)
Spanish For Dummies is the fun and easy way to learn Spanish quickly and painlessly! Written by the experts at the renowned Berlitz school, this hands-on resource shows you the ins and outs of the Spanish language and culture, acting as both a guidebook and a reference. Soon you will have all the tools you need to: Master the nuts and bolts of grammar; Greet others and introduce yourself; Get to know people with small talk; Order in restaurants; Shop anywhere; Go out on the town; Enjoy yourself with local recreation; Have a conversation on the phone; Work in an office and around the house; Ask for directions; Check in and out of a hotel; Use transportation; Call for help in an emergency.